Pengembangan Media Pembelajaran Diorama Augmented Reality pada Materi Gangguan Sistem Pernapasan Manusia untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Muhamad Syahrillah Ramadhan; Indarini Dwi Pursitasari; Santa (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low critical thinking skills of fifth-grade students at SDN Ciaruteun Ilir 03 on respiratory system disorders were caused by limited, conventional instructional media (textbooks and whiteboards), resulting in low student enthusiasm. This study aimed to develop an Augmented Reality diorama learning media on respiratory system disorders, test its feasibility, determine user responses, and analyze its effectiveness on students' critical thinking skills. The method used was Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Subjects were 25 fifth-grade students. Data were collected through observation, interviews, expert validation, response questionnaires, and critical thinking test items. Results showed the media achieved a feasibility percentage of 99% (media expert 96%, lecturer material expert 100%, teacher material expert 100%, language expert 100%), categorized as very feasible. The practicality test showed student responses of 88% and teacher responses of 96%, both very good. The effectiveness test showed the average score increased from 42.32 (pretest) to 82.86 (posttest), with an N-Gain of 0.83 (high category). Improvement was also seen across critical thinking indicators: simple explanation (34.67%→75.67%), basic skills (47%→91.33%), inference (49.67%→96.67%), further explanation (37%→93.67%), and strategy and tactics (48%→98%). The media is thus proven feasible, practical, and effective for improving students' critical thinking skills.